Baseline Assessment Towards the Implementation of Formal Sector Health Insurance Scheme for Civil Servants in Ogun State of Nigeria - Akinremi, Amos Oluwasayo; Coker, Marcellina Oluwatomi; Dosunmu, Afolabi Oladimeji; Adejumobi, Oluwabukola Moyo; Adeniregun, Adedapo Olugbenga; Edun, Folarin Opeyemi (European Journal of Applied Sciences, 2022)
The healthcare financing mechanism of a nation generally determines the access of her people to the needed qualitative and affordable health care services without undergoing any financial hardship, This study is therefore set to determine among other things the preferred mode of service payment for healthcare, as a measure of demand for health insurance, among civil servants in Ogun State of Nigeria. The study adopted a “quantitative methodology” approach, with the use of pretested self-administered questionnaires. The mean age of the respondents was 37.85 years ± standard deviation of 7.51 years. In setting the health insurance premium, majority, 59.3% of the respondents preferred government use percentage of gross salary rather than estimated amount. They suggested around 2.18% of their gross salary as premium and an additional 30.26% of their gross salary as contribution to the premium from their employer. On an average, they were only willing to pay one thousand seven hundred and eighty naira and 32 kobo (N1,780:32) in a month to have themselves, their spouse and 4 dependants covered by an health insurance scheme. The study indicated the predictors of demand for health insurance as being married, having spent 10 years and more in civil service, and perceived importance (value) of health insurance. The latter implies that there is an association between value attached to health insurance and its demand such that those who felt health insurance was important were 6 times more likely to prefer it as method of service payment than those who did not see the importance of health insurance.